Nutritional status and ergogenic aids in performance during exercise and sports - Varillas-Delgado, D. (Nutrients, 2025)
The interaction between nutritional status, ergogenic aids, and athletic performance has long been a central focus in sports science. By integrating findings from five significant studies, this editorial aims to provide a comprehensive perspective on the current landscape of nutritional interventions and their impact on exercise and sports performance. However, the practical applicability of most findings in this field remains limited, requiring careful consideration of several factors, especially in nutrition, supplementation strategies, and gene-gene interactions. Future research should prioritize larger sample sizes and include replication cohorts to enhance reliability and generalizability associations in sports science. This Special Issue, entitled "Nutritional Status and Ergogenic Aids in Performance during Exercise and Sports", compiles four recent advances and one systematic review that explore the identified gaps in knowledge and outlines future research directions.